Mock Up Website “Conato Bakery” Dengan Menerapkan Prinsip Usability - Mutiara Nur Zarima; Kartika Wulandari; Pingkan Sekar Andini; Lola Maharani Saputri; Oktafia Widya Santoso; Yanais Yalak (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2024)
In the increasingly developing digital era, website design has become one of the key elements for online business success and provides a satisfying experience for users. The usability principle is a concept related to the extent to which a website can be easily used by its users.Usability principles include Effective, Efficient, Interesting, Easy to learn and easy to remember. By applying the usability principle, a website can be effective in achieving its goals. Then there is the method used, namely the User Experience Lifecycle, which is a framework that can be applied when you want to develop a product (Prototype, Hardware and Software). There are four stages in this method, namely Analysis, Design, Implementation and Evaluation. The heuristic evaluation method is a process in which experts use rules of thumb to measure the usability of a user interface in independent search and problem reporting. The results are discussed using UX analysis methods.In designing the design has been created in a site map and innovations are adapted to solving problems. In implementation, namely implementing the design results into a web design which has its own function and evaluation applies existing usability principles.